Associação entre diabetes Mellitus e rigidez arterial central em idosos com hipertensão arterial sistêmica - Galvão, Romário Divino Vilarinho (2020)
Introduction: Aging increases the cardiovascular diseases, leading to changes in cardiovascular anatomy and physiology even in the absence of other comorbidities. Numerous cardiovascular risk factors (CVRFs), such as Diabetes Mellitus (DM) and systemic arterial hypertension (SAH), can modify the functional and structural properties of large vessels, increasing arterial stiffness. Objective: To determine whether elderly patients with hypertension and DM have greater central arterial stiffness than elderly patients with SAH without DM. Methods: The Study of Pulse Wave Velocity in the Elderly in an Urban Area in Brazil (EVOPIU) included 1,192 patients aged ≥ 60 years who underwent applanation tonometry (AT) to evaluate carotid-femoral pulse wave velocity (cfPWV). From this database, 1,133 patients were selected from 6 groups: NDN (nondiabetic normotensives; n: 127); DN (diabetic normotensives; n: 64); NDCH (nondiabetic controlled hypertensives; n: 168); DCH (diabetic controlled hypertensives; n: 275); NDH (nondiabetic hypertensives; n: 217) and DH (diabetic hypertensives; n: 282). All groups underwent AT to obtain cfPWV and central and peripheral arterial pressures. Results: The pulse wave velocities found were as follows: NDN vs DN (8.9 ± 0.2 m/s vs 9.4 ± 0.2; P = 0.103); NDCH vs DCH (9.0 ± 0.2 m/s vs. 9.6 ± 0.1 m/s; P = 0.04) and NDH vs DH (9.2 ± 0.1 m/s vs. 9.6 ± 0.1 m/s; P = 0.045). When the diabetic groups were compared, there were no differences in cfPWV values, and the same occurred when the nondiabetic groups were compared. Conclusions: Elderly patients with diabetes and hypertension have greater central arterial stiffness than patients without diabetes and hypertension, regardless of systemic blood pressure control. The central arterial stiffness caused by vascular aging seems to be a common factor among all the studied groups.